A pilot study of diffusion tensor imaging metrics and cognitive performance pre and post repetitive, intentional sub-concussive heading in soccer practice. (October 2019) - Kenny, Rebecca A; Mayo, Chantel D; Kennedy, Samantha; Varga, Aaron A; Stuart-Hill, Lynneth; Garcia-Barrera, Mauricio A; McQuarrie, Amanda; Christie, Brian R; Gawryluk, Jodie R
Background: Although soccer players routinely head the ball in practice and games, recent research has suggested that cumulative effects of repetitive heading may cause sub-concussive injury with accompanying effects on brain and behavior. The current study aimed to prospectively investigate the effects of repetitive, intentional heading in soccer practice on brain structure and cognitive function, using a within-subjects design. Methods: Participants included 10 soccer players (mean age 20.09 years ± 2.88) who were examined immediately pre- and post-heading practice. An accelerometer was used to measure the force of the impact during soccer heading. Magnetic resonance imaging data were acquired on a 3 T GE Scanner with diffusion tensor imaging. Diffusion tensor imaging analyses were completed using functional magnetic resonance imaging of the brain software library's Tract-Based Spatial Statistics to examine changes in both fractional anisotropy and mean diffusivity due to heading the soccer ball. Behavioral measures were also completed pre- and post-soccer heading and included the Sport Concussion Assessment Tool and three short-computerized executive function tasks; R studio was used to compare behavioral data within subjects. Results: Accelerometer data revealed that none of the heading impacts were >10 g . At this level of impact, there were no significant pre–post heading differences in either fractional anisotropy or mean diffusivity. Additionally, aside from minimal practice effects, there were no significant differences in Sport Concussion Assessment Tool scores and no significant differences in the performance of the three executive function tasks pre–post heading. Conclusions: The results provide initial evidence that repetitive heading in soccer practice, at a g force of 10, does not cause changes in brain structure or executive function. Future research should investigate heading in the context of games and with a greater sample size that would allow for sex-based comparisons.